Experiments to Simplify Frost Susceptibility Testing of Soils. - Kaplar,Chester W. (1971)
Experiments conducted at USA CRREL in recent years indicate that the two weeks or so required for the frost susceptibility testing of soils with previous procedures can be shortened considerably. Results of these experiments show that useful frost heaving data can be obtained in a matter of 2 or 3 days by a more rapid freezing technique. Results of experiments in which soil specimens were exposed to a constantly maintained temperature are presented. Data show that heave rate in laboratory experiments is a variable, not a constant, of a soil and is strongly dependent upon the heat extraction rate. The important role of frost susceptibility testing and soil evaluation for highway design is discussed. The suitability of equipment for use in conducting frost-heaving tests is also discussed. (Author)